Strategi STRATEGI DIGITAL MARKETING UNTUK PEMBERDAYAAN UMKM DI INDONESIA: - - Maszudi, Edi; Hapid, Hapid; Haedar, Haedar (PRIMA EKONOMIKA, 2023)
ABSTRACT The purpose of this research is to find out digital marketing strategies for empowering MSMEs in Indonesia 2021-2022. Type of data used; secondary and tertiary data. This research method: qualitative data analysis. The problem in this research: what is the digital marketing strategy for empowering MSMEs in the digital era in Indonesia? The digital marketing strategy for Indonesian MSMEs in 2021, 2022 is carried out with five strategies. First, the quality of products from MSMEs must follow the SNI (Indonesian National Standard). Second, the packaging must be attractive, healthy and unique. Third, must enter the market place and social media. Fourth, do digital branding. Fifth, give a halal label. The tough challenge is that not all MSME actors understand digital marketing. Based on data, the number of MSMEs in 2021, as many as 64 million, there are 19 million MSMEs entering the digital realm. The target of the Cooperatives and MSMEs Service is to collect as many as 14.5 million from Cooperatives, MSMEs in 2022. There are 65 million cooperatives, MSMEs in 2022. Based on data, only 19% of MSMEs have entered the digital realm. Keywords: Strategy, Digital Marketing and MSME